EFISIENSI LASER DIODA BIRU UNTUK FOTOINAKTIVASI BIOFILM Staphylococcus aureus BERDASARKAN VARIASI UMUR BAKTERI SECARA IN VITRO - HAFIDIANA, 081411331048 (2018)
This experiment was aimed to find the effect of biofilms age on the effectiveness of exposure to blue diode lasers and effective energy density of laser irradiation to inactive Staphylococcus aureus biofilm. The light source used was a blue diode laser (430,000 ± 0,007) nm with a power of (27,65 ± 0,01) mW. The experiment was used with 6 biofilms age variations and 5 energy density variations of laser irradiation and using an exposure distance of (1,00 ± 0,05) cm perpendicular to the target. The method used ELISA test to calculate OD595 value and SEM and fluorescent test to find cell death morphologically. There were control group without laser exposure and the laser exposure treatment group. The results of this experiment are the percentage of bacterial deaths. The SPSS 21 statistical test shows that there is an influence of biofilm age and energy density of laser irradiation on bacterial death in biofilms.The optimum energy density of laser irradiation was 21.16 J/cm2 to inactivate Staphylococcus aureus biofilm at each age. The percentage of death Staphylococcus aureus biofilm was 93.62% on 8 hours biofilm age, 93.31% on 16 hours biofilm age, 86.09% on 24 hours biofilm age, 81,56% on 32 hours biofilm age, 56.16% on 40 hours biofilm age and 45.30% on 48 hours biofilm age.